X-ray imaging and computed tomography of conifers treerings for climatology; ENVIROMIS-2018 - Bondarenko S. L. Svetlana Leonidovna; Batranin A. V. Andrey Viktorovich; Smirnov S. V. Sergey Vasiljevich; Stuchebrov S. G. Sergey Gennadevich (2018, 2018)
Title screen